SHIFT IN LEGAL PARADIGM FROM DECENTRALIZATION TO CENTRALIZATION IN THE MANAGEMENT OF NATURAL RESOURCES FOLLOWING THE OMNIBUS LAW ON JOB CREATION - Muhammad Juang Rambe; Wahyu Indah Sari; Danioko S. Sembiring (PT. Sinergi Legal Publisher, 2024)
The implementation of regional autonomy in Indonesia has undergone significant dynamics, particularly concerning changes in the distribution of authority between the central and regional governments. This reflects fluctuations in authority between the central and regional governments influenced by Indonesia's socio-political needs and context. During various periods, Indonesia has experienced shifts in authority, clearly evident in the Omnibus Law on Job Creation policy, which reinforces centralization in the management of vital sectors such as environmental protection, water resources, and electricity. This study employs a descriptive qualitative approach with case studies to examine the impact of this shift in authority, specifically in natural resource management following the enactment of the Omnibus Law. The research findings indicate that the Omnibus Law on Job Creation strengthens the centralization of authority within the central government, reduces the role of regional governments in natural resource management, and introduces stricter and more structured regulations, although there remains room for regions to tailor policies to local conditions. This shift affects the management of natural resources and oversight by the central government, which focuses on sustainable development and administrative efficiency. Therefore, the design of central-regional relations and the fiscal decentralization scheme must be adapted to existing needs and conditions to achieve ecological balance and sustainable social justice.